CLIMATE CHANGE ADAPTATION STRATEGIES AND TECHNICAL EFICIENCY ANALYSIS OF RICE FARMING IN BABAAN HAMLET, NGENEP VILLAGE, KARANGPLOSO, MALANG - Aura, Bintang Athala; Rini Mutisari; Fahriyah; Deny Meitasari (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
Increasing the amount of rice production is needed to meet the needs of rice as the main food of the Indonesian people. One of the efforts that can be made to increase production and or productivity is to use inputs efficiently. Efficient use of inputs can be influenced by the managerial ability of farmers, where the managerial ability of farmers can have an impact on technical inefficiency. Farmers in Babaan Hamlet as the research location are suspected to be technically inefficient. Some of the causes include management capabilities derived from social factors and the ability to adapt to climate change. Therefore, the objectives of this study are to analyze the factors that affect rice production, analyze the technical efficiency of rice farming in Babaan Hamlet, and analyze the factors that affect technical inefficiency. The method used to answer the first and second objectives is Stochastic Frontier Analysis (SFA) with Cobb Douglass production function and Maximum Likelihood Estimation (MLE) approach. While the third objective was answered by using tobit regression analysis. The results showed that rice farming in Babaan Hamlet has not been technically efficient, which has an average of 58% so that it can still be increased by 42%. Factors that positively affect the amount of production are land area and the amount of pesticides. Meanwhile, social factors that negatively affect inefficiency include education and frequency of participation in counseling. On the other hand, the number of adaptation strategies to climate change has a positive effect on technical inefficiency.